Organophosphate Pesticide Exposure on Erythrocyte Acetylcholinesterase Activity and Health Effects in Agricultural Workers - Sanda Kyaw (Myanmar Medical Journal, 2026)
"Organophosphate (OP) pesticides are extensively used in agriculture, notably in Myanmar, posing significant health risks to farming populations through occupational exposure. Such exposure primarily inhibits erythrocyte acetylcholinesterase (AChE) activity, serving as a biomarker for systemic toxicity. The present review compiles findings from local and global studies demonstrating that chronic OP pesticide exposure leads to a marked decrease in erythrocyte AChE activity, correlating with adverse health effects including respiratory dysfunction, immune dysregulation characterized by increased inflammatory cytokine and oxidative stress marker such as IL-6 and serum malondialdehyde levels, and increased insulin resistance and cardiovascular disease risk. Moreover, in condition of prolonged exposure to pesticides, there would be activation of endoplasmic reticulum, ER stress pathway and ER stress might be the link between pesticide exposure and development of long-term adverse health effects. The evidence empha